Discovery of a 6-Aminobenzo[b]thiophene 1,1-Dioxide Derivative (K2071) with a Signal Transducer and Activator of Transcription 3 Inhibitory, Antimitotic, and Senotherapeutic Activities - Oleksak, Patrik; Rysanek, David; Vancurova, Marketa; Vasicova, Pavla; Urbancokova, Alexandra; Novak, Josef; Maurencova, Dominika; Kashmel, Pavel; Houserova, Jana; Mikyskova, Romana; Novotny, Ondrej; Reinis, Milan; et al. (ACS pharmacology & translational science, 2024)
6-Nitrobenzo[b]thiophene 1,1-dioxide (Stattic) is a potent signal transducer and activator of the transcription 3 (STAT3) inhibitor developed originally for anticancer therapy. However, Stattic harbors several STAT3 inhibition-independent biological effects. To improve the properties of Stattic, we prepared a series of analogues derived from 6-aminobenzo[b]thiophene 1,1-dioxide, a compound directly obtained from the reduction of Stattic, that includes a methoxybenzylamino derivative (K2071) with optimized physicochemical characteristics, including the ability to cross the blood-brain barrier. Besides inhibiting the interleukin-6-stimulated activity of STAT3 mediated by tyrosine 705 phosphorylation, K2071 also showed cytotoxicity against a set of human glioblastoma-derived cell lines. In contrast to the core compound, a part of K2071 cytotoxicity reflected a STAT3 inhibition-independent block of mitotic progression in the prophase, affecting mitotic spindle formation, indicating that K2071 also acts as a mitotic poison. Compared to Stattic, K2071 was significantly less thiol-reactive. In addition, K2071 affected cell migration, suppressed cell proliferation in tumor spheroids, exerted cytotoxicity for glioblastoma temozolomide-induced senescent cells, and inhibited the secretion of the proinflammatory cytokine monocyte chemoattractant protein 1 (MCP-1) in senescent cells. Importantly, K2071 was well tolerated in mice, lacking manifestations of acute toxicity. The structure-activity relationship analysis of the K2071 molecule revealed the necessity of the para-substituted methoxyphenyl motif for antimitotic but not overall cytotoxic activity of its derivatives. Altogether, these results indicate that compound K2071 is a novel Stattic-derived STAT3 inhibitor and a mitotic poison with anticancer and senotherapeutic properties that is effective on glioblastoma cells and may be further developed as an agent for glioblastoma therapy.